The Pediatric Critical Care Transfusion and Anemia Expertise Initiative Consensus Conference Methodology. (September 2018) - Bembea, Melania M.; Valentine, Stacey L.; Bateman, Scot T.; Wilson, Lisa M.; Anton, Blair; Harger, Nancy; Robinson, Karen A.
Abstract : Objectives: This article describes the methodology used for Pediatric Critical Care Transfusion and Anemia Expertise Initiative Consensus Conference. Design: Consensus conference of international experts in pediatric critical care and transfusion medicine, following standards set by the Institute of Medicine, using the Research and Development/UCLA Appropriateness Method, modeled after the Pediatric Acute Lung Injury Consensus Conference. Topics related to RBC transfusion in children with or at risk for critical illness were divided into nine subgroups with a systematic review of the literature. Methods: The panel of 38 content and four methodology experts met three times over the course of 2 years and collaborated to develop evidence-based and, when evidence was lacking, expert-based clinical recommendations as well as research priorities for RBC transfusions in critically ill children or those at risk for critical illness. Electronic searches were conducted using PubMed, Embase, and Cochrane Library databases from 1980 to May 2017. Agreement was obtained using the Research and Development/UCLA Appropriateness Method. We used a standardized data extraction form to construct evidence tables and graded the evidence using the Grading of Recommendations Assessment, Development, and Evaluation system. Main Results: The consensus conference resulted in 102 recommendation statements, of which 57 were clinical (20 evidence based and 37 based on expert consensus) and 45 detailed recommendations for future research. Dissemination was done via decision tree, a primary publication listing all statements, and separate publications for each subtopic that include supporting arguments for each recommendation. Conclusions: A consensus conference of experts from around the world developed recommendations for RBC transfusions in critically ill children or children at risk for critical illness, the identification of current research gaps, and future research priorities. Abstract : Supplemental Digital Content is available in the text.